The Relationship of Environmental Sanitation and Hygiene Behavior with Stunting Incidents in Adults in 2024 - Prihayati; Sunawati; Marthia Ikhlasiah (Nursing and Health Sciences Journal (NHSJ), 2024)
The incidence of stunted (short) toddlers is the main nutritional problem faced by Indonesia based on Nutritional Status Monitoring (PSG) data for the last three years. This thesis aims to determine the distribution of environmental sanitation and hygiene behavior on the incidence of stunting in toddlers. This research uses a quantitative approach with the technique of distributing questionnaires containing statements for each research variable. The research sample consisted of 44 mothers of toddlers who had children with stunting. The results of the research show that there is no relationship between environmental sanitation and the incidence of stunting in Baduta in the Industrial Area of ​​the Citangkil II Health Center, Cilegon City, with a value of p = 0.054 which is greater than α = 0.05, which can be interpreted as meaning that there is no relationship. There is a significant relationship between environmental sanitation and the incidence of stunting in Baduta with an Odds Ratio value of (OR) = 4.048, and there is a relationship between hygiene behavior and the incidence of stunting in Baduta in the Industrial Area of ​​the Citangkil II Health Center, Cilegon City, with a p value of more than 0.008. smaller than α= 0.05 which can be interpreted as meaning that there is a significant relationship between hygiene behavior and the incidence of stunting in Baduta with an Odds Ratio value of (OR) = 1.929.The conclusion in this study is that hygiene behavior factors are related to the incidence of stunting but vice versa with environmental sanitation. Several things that can be suggested based on the research results are socializing hygiene practices in the community.